The Corporate Governance of National Security - Andrew Verstein (Washington University Law Review, 2018)
At hundreds of companies, the government installs former spies and military officers to run the business without shareholder oversight, putting security before profits in order to protect vital projects from potentially treasonous influences. Through procedures I call “National Security Corporate Governance,” corporate boardrooms have quietly become instruments of national defense, marrying the efficiency norms of corporate law and the protective ambitions of national security. How is this achieved, and how successfully? Using a variety of research approaches – including Freedom of Information Act (FOIA) requests, archival searches, telephone interviews, and in-person conversations with industry insiders – this Article illuminates a secretive government program and the challenging questions regarding the relationship between private ordering and public goals such as national security.
Keywords: National Security; Corporation; Corporate Law; Corporate; Corporate Governance; Freedom of Information Act; FOIA; Outside Directors; Inside Directors; Proxy Holders; Shareholder-Centrism; Information Security; Industrial Security; Unity; FOCI; Military-Industrial Complex